On addressing privacy in disseminating judicial data: towards a methodology. Issue 1 (20th March 2017) - Bargh, Mortaza S.; Choenni, Sunil; Meijer, Ronald
Abstract : Purpose: Information dissemination has become a means of transparency for governments to enable the visions of e-government and smart government, and eventually gain, among others, the trust of various stakeholders such as citizens and enterprises. Information dissemination, on the other hand, may increase the chance of privacy breaches, which can undermine those stakeholders' trust and thus the objectives of transparency. Moreover, fear of potential privacy breaches compels information disseminators to share minimum or no information. The purpose of this study is to address these contending issues of information disseminations, i.e. privacy versus transparency, when disseminating judicial information to gain (public) trust. Specifically, the main research questions are: What is the nature of the aforementioned "privacy–transparency" problem and how can we approach and address this class of problems? Design/methodology/approach: To address these questions, the authors have carried out an explorative case study by reconsidering and analyzing a number of information dissemination cases within their research center for the past 10 years, reflecting upon the whole design research process, consulting peers through publishing a preliminary version of this contribution and embedding the work in an in-depth literature study on research methodologies, wicked problems and e-government topics. Findings: The authors show that preserving privacy while disseminating information for transparency purposes is a typical wicked problem, propose an innovative designerly model called transitional action design research (TADR) to address the class of such wicked problems and describe three artifacts which are designed, intervened and evaluated according to the TADR model in a judicial research organization. Originality/value: Classifying the privacy transparency problem in the judicial settings as wicked is new, the proposed designerly model is innovative and the realized artifacts are deployed and still operational in a real setting.